Interleukin-4 down-regulates MHC class II antigens on cultured rat astrocytes - Morga, Eleonora; Heuschling, Paul (Glia, 1996)
Mammalian cerebral astrocytes can be brought to express major histocompatibility complex (MHC) class II molecules upon appropriate stimulation. It is well established that this expression is subject to modulation by several neurotransmitters and cytokines. We show that the low, basal expression of MHC class II antigens on cultured rat astrocytes is concentration‐dependently down‐regulated by low concentrations of interleukin‐4 (IL‐4), reaching maximal inhibition at 10 U/ml. The higher, γ‐IFN‐induced, expression of class II molecules is also decreased by increasing concentrations of IL‐4, significant effects being already observed at 5 U/ml. Since the cAMP as well as the nitric oxide dependent cGMP pathway have previously been shown to mediate an inhibition on astroglial MHC class II expression, we measured the intra‐cellular content of cyclic nucleotides after stimulation with IL‐4. No rise in cAMP or cGMP is detected. Similarly, IL‐4 does not affect the induced synthesis of nitric oxide radicals. Since MHC class II expression is a critical step in many regulatory processes of the cellular immune reaction, IL‐4, via its activity on astroglial cells, emerges as an important modulator of immunological activities in the central nervous system. © 1996 Wiley‐Liss, Inc.